Hukum Penisbahan Sifat Pencipta pada Manusia dan Hubungannya dengan Pemahaman Qadariyah - Abdullah Nazhim Hamid; Rifai, Awal (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This research was aiming to know the rule of atribution of creator to mandkind and its relation to the Qadariyahâ€™s believes. This research used the library review methods by collecting the views of the scholars from the linguist of Arabic Langiage, Quran Interpreters, and generalist scholars which are have concern abaout the Islamic doctrines. The Result of The Research showed that of word al-khalqu in Arabic has two meanings, the first meaning is to put something out of nothingness to existance and the second is to invent or make or produce or transform of one nature into another. Therefore, the rule of this atribituon is depends on two conditions, the purpose of using the word â€œcreatorâ€ and its object. If the word â€œcreatorâ€ based on the second meaning, and the object is the things are still in human capacity and reasoning then the using is allowed. However, if those two conditions are not fulfilled, then the using is prohibited. Moreover, if the attribution is related to the human act and accompanied by the belief that there is no divine intervention and human is the main cause of his creation, then it is closely related to the Qadariyah understanding.